Aesthetic labour and the policy-making agenda: time for a reappraisal of skills? - Nickson, D; Warhurst, C; Dutton, E (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2004)
Previous research in the area of 'aesthetic labour' has suggested that 'aesthetic skills' are important in interactive service work, such as retail and hospitality. To-date, research on aesthetic labour has merely pointed to the existence of aesthetic skills, but there has been no real attempt to examine the extent of the demand for such skills. This paper seeks to rectify this omission. It reports on a survey undertaken in the Glasgow retail and hospitality labour markets by examining labour demand in terms of recruitment and selection, skills and training. The findings point to a high level of demand for aesthetic skills in retail and hospitality. Pursuant on this identification of the demand for such skills we consider apposite policy responses, suggesting that there is increasingly a need for a reappraisal of skills in the current, service-dominated economy.